Productivity Unplugged : The Challenges of Malaysia's Transition into a High-Income Country - World Bank Group (World Bank, Washington, DC, 2018)
As Malaysia continues to strive toward high-income status, accelerating productivity growth has become the country’s central economic policy challenge. Productivity growth has become increasingly important as the country’s traditional economic engines have slowed. Declining oil and gas output, coupled with the slowing growth of the Malaysian mining sector, has reduced the pace of capital accumulation, while demographic trends are slowing the growth of the labor force. Demographic trends underscore the vital importance of productivity growth to the continued development of the Malaysian economy. Malaysia’s demographic transition is inhibiting the expansion of the labor supply, and female labor-force participation is low by the standards of comparable countries. Weakening external demand and intensifying global competition in Malaysia’s key export industries confirm the necessity of increasing productivity levels. The report presents an empirical analysis of the role of productivity in the Malaysian economy. It evaluates the country’s institutional and policy framework, and identifies key constraints to productivity growth. Using time-series data and cross-country comparisons, the report examines the ways in which infrastructure and institutional quality, market efficiency, innovation, and workforce skills influence productivity in Malaysia. This analysis is designed to inform a productivity-focused economic agenda, and the report concludes by presenting a set of policy recommendations and institutional reforms designed to bolster long-run productivity growth.